Takayasu’s arteritis: what should the dentist know? - C. DUQUE, R. C. SILVA & L. SANTOS-PINTO (Paediatric Dentistry, 2005)
The first published report on Takayasu’s arteritis (TA) was made in 1908 by the ophthalmologist Mikito Takayasu, who reported ocular changes such as aneurysms and arteriovenous anastomoses in patients with this disease [1].